Efficacy of fingolimod in patients with highly active relapsing–remitting multiple sclerosis. (2nd September 2015) - Derfuss, T.; Bergvall, N.K.; Sfikas, N.; Tomic, D.L.
Abstract: Objective: There is a need to identify effective switch therapies for patients with relapsing–remitting multiple sclerosis (RRMS) who experience high disease activity despite receiving disease-modifying therapy (DMT). The objective of this study was to assess the efficacy of fingolimod versus placebo in patients with RRMS who had experienced high disease activity despite previously receiving DMT, using post hoc analyses of two phase 3 trials: FREEDOMS (NCT00289978) and FREEDOMS II (NCT00355134). Research design and methods: Clinical and magnetic resonance imaging outcomes over 24 months were analyzed in patients from FREEDOMS and FREEDOMS II who had received treatment in the previous year and had: (1) ≥1 relapse in the previous year and either ≥1 gadolinium (Gd) enhancing T1 lesion or ≥9 T2 lesions at baseline and/or (2) as many or more relapses in the year before baseline as in the previous year (as per fingolimod's EU label). Main outcome measures: The inclusion criteria were fulfilled by 249 and 257 patients in the fingolimod and placebo groups, respectively. Annualized relapse rates were reduced by 48% for fingolimod versus placebo ( p  < 0.001). Fingolimod reduced the risk of 3 month and 6 month confirmed disability progression by 34% ( p  = 0.031) and 45% ( p  = 0.016), respectively, versus placebo. Brain volume loss was reduced by 46% for fingolimod versus placebo ( p  < 0.001). The reduction in Gd-enhancing T1 lesion counts for fingolimod versus placebo was 65% ( p  < 0.001). Furthermore, fingolimod reduced the number of new or newly enlarged T2 lesions by 69% relative to placebo ( p  < 0.001). Limitation: The analyses are post hoc, but the population is specified by the European Medicines Agency in the label for fingolimod. Conclusions: Fingolimod demonstrated efficacy across all four key RRMS disease measures analyzed in patients with high disease activity despite previous DMT.